Exploring Knowledge, Attitudes, and Practice Associated With Meditation Among Patients With Melanoma. (June 2018) - Russell, Lahiru; Orellana, Liliana; Ugalde, Anna; Milne, Donna; Krishnasamy, Meinir; Chambers, Richard; Livingston, Patricia M.
Aim: To explore the knowledge, attitudes, and practices associated with meditation among people with melanoma and investigate the relationship between perceived stress, trait mindfulness, and meditation. Factors associated with interest to participate in an online meditation program were also explored.Methods: A survey-based cross-sectional study of 291 patients attending a melanoma outpatient clinic assessed knowledge of meditation, attitudes toward meditation using Determinants of Meditation Practice Inventory (DMPI), and meditation experience. Perceived stress and trait mindfulness were measured using the Perceived Stressed Scale and Cognitive and Affective Mindfulness Scale, respectively.Results: Participants who had tried meditation (43%) were likely to be younger, female, and have completed higher education or be employed. Perceived stress score was higher among women, younger participants, and those treated in the past year but did not differ by melanoma stage. Participants reported a good understanding of the potential benefits of meditation, but even among people with meditation experience, common misconceptions prevailed. The main barrier to meditation was a perceived lack of knowledge about meditation . Higher DMPI scores were associated with lower education, moderate to low access to service centers, or living in disadvantaged neighborhoods . Participants practicing meditation that involved self-reflection reported less stress and higher trait mindfulness compared with participants practicing another type of meditation. People interested in participating in an online meditation-based program reported higher perceived stress than those not interested.Conclusion: A meditation-based intervention teaching self-reflective practices, targeted at people with melanoma, may have the potential to assist them with managing their stress.